POSSIBILITY TO ESTIMATE BULK PERMEABILITY FROM SEISMIC DATA - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 2006)
Permeability is one of the most important reservoir parameter which determines the reserves. Unlike the porosity which is considered to be the static property of oil and gas reservoir, permeability is the dynamic property. It reflects the ability of reservoir rock to transmit fluid (oil gas or water). The reservoir rock is located deep below the subsurface, so that the measurement of the permeability is usually carried out from the cores. So far there is no well logging tool which measures the rock permeability directly. Physically, there is no direct relationship between porosity and permeability, the estimation of permeability from the cross-plot between porosity and permeability is just a rough estimate, but it is usually accepted in practical application. Apart from cross- correlation method, there is now exist a sophisticated approach to estimate permeability based on well log data using artificial neural network. There now exist a method which is widely accepted to estimate the porosity of the subsurface layer using seismic method. This method exploits the relationship between porosity and acoustic impedance of the sub- surface layer. And since acoustic impedance can be derived from the seismic amplitudes, it means that the rock porosity can be estimated from seismic data. A new question can be exposed as follows :